Systematic review and meta-analysis of birth weight and prenatal exposure to perfluoroundecanoic acid - Hongyu Ru; Paige A. Bommarito; Michael W. Dzierlenga; Alexandra L. Lee; Kristen M. Rappazzo; Benjamin J.K. Davis; Avanti V. Shirke; Alexis Agbai; Elizabeth G. Radke; Thomas F. Bateson; J. Michael Wright (Environmental Research, 2026)

Use of Unmanned Aerial Vehicles in Precision Agriculture: An Exploration of Remotely Sensed Data and Methods for Monitoring Corn Varieties - Benjamin T. Fraser; Russell G. Congalton; Peter H. Davis; Tom Beaudry; Carl Majewski; Aaron Palmer (Agricultural Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Global estimates of women's and men's employment in agrifood systems from 2000 to 2021 - Valentina Costa; Natalia Piedrahita; Erdgin Mane; Benjamin Davis; Vanya Slavchevska (Global Food Security, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Corrigendum to “Association between summertime emergency department visits and maximum daily heat index in rural and non-rural areas of Virginia (2015–2022)” [Sci. Total Environ. Volume 948 (2024) 174753] - Antonia Mendrinos; Janice O'Brien; Meredith Davis; Alexandra Baldwin; Benjamin F. Zaitchik; Annie Britton; Immaculata Mwanja; Julia M. Gohlke (Science of The Total Environment, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Wellbeing dynamics in sub-Saharan Africa: a spatial perspective across territorial typologies - Luis G. Becerra–Valbuena; Nicholas J. Sitko; Ana Paula De la O Campos; Benjamin Davis; Stefanija Veljanoska (Journal of Rural Studies, 2025)

Gender Inequalities in Agrifood Systems: An overview of the state of research - Lauren Phillips; Agnes Quisumbing; Vanya Slavchevska; Benjamin Davis; Talip Kilic; Erdgin Mane (Global Food Security, 2025)

Limited ARG removal but stable resistome dynamics in a surface flow constructed wetland - Benjamin C. Davis; David Linz; Brian R. McMinn; Asja Korajkic (Journal of Environmental Management, 2025)

Resilient and inclusive rural transformation: Pathways towards improved nutrition - Ramya Ambikapathi; Kaleab Baye; Romina Cavatassi; Kate Schneider Lecy; Benjamin Davis; Lynnette M. Neufeld (Global Food Security, 2025)

The agrifood-system wage gap and structural transformation: cross-country evidence - Marwan Benali; Vanya Slavchevska; Natalia Piedrahita; Benjamin Davis; Nicholas Sitko; Carlo Azzarri; Gianluigi Nico; Dung Thi Le; Jessika Kluth (Global Food Security, 2025)

Resilient and inclusive rural transformation: Exploring pathways for sustainable development - Benjamin Davis; Romina Cavatassi; Leslie Lipper; Ken E. Giller (Global Food Security, 2025)

Evaluation of processed soy ingredients for largemouth bass (Micropterus nigricans) fingerlings on growth performance, intestinal health, and disease susceptibility - Jamison L. Semla; Ian A.E. Butts; D. Allen Davis; Abdulmalik A. Oladipupo; Benjamin R. LaFrentz; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

Comparison of camera traps, eDNA, and visual encounter surveys for threatened species detection - Leah R.N. Samuels; Taylor Wilcox; Michelle Hoffman; Michele Elmore; Robert Aldredge; Benjamin S. Stegenga; James E. Bogan Jr.; Mark A. Davis; Stephanie Hertz; Michael K. Schwartz; Houston C. Chandler (Journal for Nature Conservation, 2025)

Influence of dietary fermented yeast products (Saccharomyces cerevisiae) on performance, health and microbiome of Nile tilapia (Oreochromis niloticus) and the influence of discharge water in the production of romaine lettuce (Lactuca sativa) - Uthpala M. Padeniya; D. Allen Davis; Daniel E. Wells; Courtney E. Harrison; Benjamin R. LaFrentz; Benjamin H. Beck; Luke A. Roy; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

Adsorption of MC-LR enabled by customizable 3D printed graphene-coated structures - Justin D. Puhnaty; Jacob M. Lalley; Alan J. Kennedy; Jaylen A. Davis; Angela M. Evans; Sarah Grace Zetterholm; Connor C. Clark; Jesse L. Roberts; Christopher S. Griggs; Benjamin S. Magbanua (Journal of Environmental Chemical Engineering, 2025)

Decreasing farm sizes and the viability of smallholder farmers: Implications for resilient and inclusive rural transformation - Sarah K. Lowder; Garima Bhalla; Benjamin Davis (Global Food Security, 2025)

Genetic structure of Ethiopian finger millet landraces and genome-wide association mapping for agronomic and nutritional traits - Adane Gebreyohannes; Hussein Shimelis; Davis M. Gimode; Prasad Grandham; Vinod Kumar Valluri; Habte Nida; Susan M. Moenga; Chris O. Ojiewo; Benjamin Kilian; Damaris A. Odeny (Theoretical and Applied Genetics, 2025)
Finger millet ( Eleusine coracana subsp. coracana ) (2n = 4x = 36) remains one of the most important millets in East Africa (EA), where it was most likely domesticated along the highlands of Ethiopia and Uganda. The goal of the current study was to understand the population structure of the Ethiopian finger millet landraces and identify quantitative trait nucleotides (QTNs) and haplotypes associated with agronomic and nutritional traits. In a field evaluation across three environments, 448 genotypes were assessed for days to flowering (DTF), days to maturity (DTM), thousand seed weight (TSW), grain yield (GY), stay-green score (STG), and drought score (DrtSc). The harvested grain was analyzed for Fe and Zn contents. A subset of 391 genotypes was skim-sequenced, generating 24,112 high-quality SNPs that were employed for population structure, association mapping, and haplotype analysis. Seventy marker-trait associations were detected including 15 major QTNs with more than 30% phenotypic variance explained (PVE) for all traits except STG and GY. Pleiotropic major QTNs were identified for DTM/DTF and Fe/Zn on chromosomes 9B and 2B, respectively. Haplotype analysis of major QTNs identified 54 significant haplotype blocks and 2 additional haplotypes for a multidrug ABC transporter gene family like protein on chromosome 4A that was associated with PTH. Favorable haplotypes from pleiotropic DTM/DTF and Fe/Zn QTNs were present in 13 and 12 genotypes respectively, majority from Tigray region. Two genotypes from Tigray and one from Amhara harbored favorable haplotypes for DTM/DTF and Fe/Zn. These findings provide invaluable insights for targeted breeding to enhance finger millet resilience, nutritional profile, and yield.

Subsewershed analyses of the impacts of inflow and infiltration on viral pathogens and antibiotic resistance markers across a rural sewer system - Amanda Darling; Benjamin Davis; Thomas Byrne; Madeline Deck; Gabriel Maldonado Rivera; Sarah Price; Amber Amaral-Torres; Clayton Markham; Raul Gonzalez; Peter Vikesland; Leigh-Anne Krometis; Amy Pruden; et al. (Water Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Microplastic biomonitoring studies in aquatic species: A review & quality assessment framework - Benjamin de Jourdan; Danielle Philibert; Davide Asnicar; Craig Warren Davis (Science of The Total Environment, 2024)

Resilient and inclusive rural transformation in sub-Saharan Africa under climate, demographic, and social change: Challenges and opportunities for income growth and job creation - Kate R. Schneider; Ana Paula De la O Campos; Romina Cavatassi; Benjamin Davis (Global Food Security, 2024)

Whither the agricultural productivity-led model? Reconsidering resilient and inclusive rural transformation in the context of agrifood systems - Benjamin Davis; Ana Paula de la O Campos; Mohammad Farrae; Paul Winters (Global Food Security, 2024)

Assessment of dietary yeast‐based additives for cultured catfish and tilapia health - Guillaume Cacot; D. Allen Davis; Benjamin R. LaFrentz; Mark R. Liles; Ian A. E. Butts; Craig A. Shoemaker; Benjamin H. Beck; Mark Farmer; Timothy J. Bruce (Journal of Fish Diseases, 2024)
Channel catfish ( Ictalurus punctatus ) and Nile tilapia ( Oreochromis niloticus ) are two aquaculture species of great importance. Intensive production is often hindered by poor growth performance and disease mortality. The aim of this study was to evaluate the potential of a commercial fermented yeast product, DVAQUA, on channel catfish and Nile tilapia growth performance metrics and disease resistance. Channel catfish and Nile tilapia were fed practical diets supplemented with 0%, 0.1% or 0.4% of DVAQUA over approximately 2‐month feeding periods in recirculation aquaculture systems. To assess the potential of the postbiotic against common aquaculture pathogens, juvenile catfish were subsequently challenged by immersion with Edwardsiella ictaluri S97‐773 or virulent Aeromonas hydrophila ML09‐119. Nile tilapia juveniles were challenged by injection with Streptococcus iniae ARS‐98‐60. Serum lysozyme activity, blood chemistry and growth metrics were measured at the end of the feeding period, but no differences were observed across the different metrics, except for survival. For the pathogen challenges, there were no differences in endpoint mortality for channel catfish with either pathogen ( p > .05). In contrast, Nile tilapia survivability to S. iniae infection increased proportionally to the inclusion of DVAQUA ( p = .005). Changes to sera lysozyme activity were also noted in the tilapia trial, with a reduction of activity in the fish fed the 0.4% DVAQUA diet compared to the control diet ( p = .031). Expression profiles of proinflammatory genes and antibodies were also found to be modulated in channel catfish fed the postbiotic, indicating some degree of protective response. These results suggest that this postbiotic may be beneficial in protecting Nile tilapia against S. iniae infection by influencing immune parameters and additional research is needed to evaluate the potential of this DVAQUA for improving catfish health and disease control.

Association between summertime emergency department visits and maximum daily heat index in rural and non-rural areas of Virginia (2015–2022) - Antonia Mendrinos; Janice O'Brien; Meredith Davis; Alexandra Baldwin; Benjamin F. Zaitchik; Annie Britton; Immaculata Mwanja; Julia M. Gohlke (Science of The Total Environment, 2024)

Oxadiazole derivatives as stable anolytes for >3 V non-aqueous redox flow battery - Kate A. Jesse; Sergio Diaz-Abad; Christopher E. Van Pelt; Emily Pentzer; Benjamin L. Davis; Sandip Maurya (Chemical Engineering Journal, 2024)

Growth hormone-receptor disruption in mice reduces osteoarthritis and chondrocyte hypertrophy - Huanhuan Liu; Trent Davis; Silvana Duran-Ortiz; Tom Martino; Austin Erdely; Shane Profio; Benjamin Osipov; Gabriela G. Loots; Darlene E. Berryman; Patrick M. O’Connor; John J. Kopchick; Shouan Zhu (GeroScience, 2024)
Excessive growth hormone (GH) has been shown to promote joint degeneration in both preclinical and clinical studies. Little is known about the effect of disrupted GH or GH receptor (GHR) on joint health. The goal of this study is to investigate joint pathology in mice with either germline ( GHR -/- ) or adult inducible ( iGHR -/- ) GHR deficiency. Knee joints from male and female GHR -/- and WT mice at 24 months of age were processed for histological analysis. Also, knee joints from male and female iGHR -/- and WT mice at 22 months of age were scanned by micro-CT (μCT) for subchondral bone changes and characterized via histology for cartilage degeneration. Joint sections were also stained for the chondrocyte hypertrophy marker, COLX, and the cartilage degeneration marker, ADAMTS-5, using immunohistochemistry. Compared to WT mice, GHR -/- mice had remarkably smooth articular joint surfaces and an even distribution of proteoglycan with no signs of degeneration. Quantitatively, GHR -/- mice had lower OARSI and Mankin scores compared to WT controls. By contrast, iGHR -/- mice were only moderately protected from developing aging-associated OA. iGHR -/- mice had a significantly lower Mankin score compared to WT. However, Mankin scores were not significantly different between iGHR -/- and WT when males and females were analyzed separately. OARSI scores did not differ significantly between WT and iGHR -/- in either individual or combined sex analyses. Both GHR -/- and iGHR -/- mice had fewer COLX + hypertrophic chondrocytes compared to WT, while no significant difference was observed in ADAMTS-5 staining. Compared to WT, a significantly lower trabecular thickness in the subchondral bone was observed in the iGHR -/- male mice but not in the female mice. However, there were no significant differences between WT and iGHR -/- mice in the bone volume to total tissue volume (BV/TV), bone mineral density (BMD), and trabecular number in either sex. This study identified that both germline and adult-induced GHR deficiency protected mice from developing aging-associated OA with more effective protection in GHR -/- mice.

Systems analysis for energy assets of Iraq influenced by water scarcity - Megan C. Marcellin; Gigi Pavur; Davis C. Loose; John J. Cardenas; David Denehy; Mustafa Almashhadani; Saddam Q. Waheed; Benjamin D. Trump; Thomas L. Polmateer; Igor Linkov; Venkataraman Lakshmi; James H. Lambert (Environment Systems and Decisions, 2024)
Water security in arid and semi-arid Middle Eastern climates has been severely impacted by effects of climate change such as reduced precipitation, diminished storage, increased evapotranspiration, and prolonged heat waves. These climate effects are compounded in Iraq, where populations, agriculture, industry, and energy rely heavily on varying transboundary water flows to meet water demands. Iraq’s most profitable sector, energy, is especially threatened by insufficient water supply, which complicates government decision making in energy infrastructure development. The goal of this paper is to develop a scenario-based multi-criteria analysis framework to prioritize infrastructure investments in the context of climate change and scarcity of natural resources. Infrastructure facilities are evaluated against social, economic, climate, and hydrologic criteria across a set of disruptive climatological, economic, and social scenarios to identify robust initiatives and the most and least disruptive scenarios to the system. A particular innovation of this paper is the evaluation of hydrology data derived from satellites in determining water scarcity impact on individual energy facilities. The methods are demonstrated for a critical sector of Iraq’s economy: oil and natural gas. The demonstration includes 13 system-order criteria, 44 oil and gas initiatives within Iraq, and seven risk scenarios. The results include an accounting of the most and least disruptive scenarios to energy sector priorities and scenario-based system orderings to guide stakeholders in investment prioritization.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Opportunities for regional collaboration and prevention: Assessing the risk of the live bait trade as a pathway of invasive species - Hannah Mulligan; Benjamin J. Schall; Tanner Davis; Alison A. Coulter (Biological Conservation, 2023)

Recommendations for the use of metagenomics for routine monitoring of antibiotic resistance in wastewater and impacted aquatic environments - Benjamin C. Davis; Connor Brown; Suraj Gupta; Jeannette Calarco; Krista Liguori; Erin Milligan; Valerie J. Harwood; Amy Pruden; Ishi Keenum (Critical Reviews in Environmental Science and Technology, 2023)

Probiotics enhance resistance to Streptococcus iniae in Nile tilapia ( Oreochromis niloticus ) reared in biofloc systems - Uthpala Padeniya; D. Allen Davis; Mark R. Liles; Stacey A. LaFrentz; Benjamin R. LaFrentz; Craig A. Shoemaker; Benjamin H. Beck; Daniel E. Wells; Timothy J. Bruce (Journal of Fish Diseases, 2023)
Biofloc technology is a rearing technique that maintains desired water quality by manipulating carbon and nitrogen and their inherent mixture of organic matter and microbes. Beneficial microorganisms in biofloc systems produce bioactive metabolites that may deter the growth of pathogenic microbes. As little is known about the interaction of biofloc systems and the addition of probiotics, this study focused on this integration to manipulate the microbial community and its interactions within biofloc systems. The present study evaluated two probiotics ( B. velezensis AP193 and BiOWiSH FeedBuilder Syn 3) for use in Nile tilapia ( Oreochromis niloticus ) culture in a biofloc system. Nine independent 3785 L circular tanks were stocked with 120 juveniles (71.4 ± 4.4 g). Tilapia were fed for 16 weeks and randomly assigned three diets: a commercial control diet or a commercial diet top‐coated with either AP193 or BiOWiSH FeedBuilder Syn3. At 14 weeks, the fish were challenged with a low dose of Streptococcus iniae (ARS‐98‐60, 7.2 × 10 7 CFU mL −1 , via intraperitoneal injection) in a common garden experimental design. At 16 weeks, the fish were challenged with a high dose of S. iniae (6.6 × 10 8 CFU mL −1 ) in the same manner. At the end of each challenge trial, cumulative per cent mortality, lysozyme activity and expression of 4 genes ( il‐1β , il6 , il8 and tnfα ) from the spleen were measured. In both challenges, the mortalities of the probiotic‐fed groups were significantly lower ( p S. iniae . Nonetheless, overall il6 expression was lower in fish challenged with a high dose of ARS‐98‐60, while tnfα expression was lower in fish subjected to a lower pathogen dose. Study findings demonstrate the applicability of probiotics as a dietary supplement for tilapia reared in biofloc systems.

On demand feeding and the response of Pacific white shrimp (Litopenaeus vannamei) to varying dietary protein levels in semi-intensive pond production - Leila M. Strebel; Khanh Nguyen; Adela Araujo; Trenton Corby; Melanie Rhodes; Benjamin H. Beck; Luke A. Roy; D. Allen Davis (Aquaculture, 2023)

Task impairment: A novel approach for assessing impairment during exploration-class spaceflight missions - William Fernandez; Dana Levin; Jon G. Steller; Eric Kerstman; Jay Lemery; Christopher Zahner; Hillary E. Davis; Kris Lehnhardt; Benjamin Easter; Amy J. Kreykes (Journal of Space Safety Engineering, 2023)

Genomic analysis of Bornean geckos (Gekkonidae: Cyrtodactylus ) reveals need for updated taxonomy - Hayden R. Davis; Izneil Nashriq; Kyra S. Woytek; Shanelle A. Wikramanayake; Aaron M. Bauer; Benjamin R. Karin; Ian G. Brennan; Djoko T. Iskandar; Indraneil Das (Zoologica Scripta, 2023)
Using molecular genetic data, recognised diversity within the gecko genus Cyrtodactylus has more than doubled, with many lineages that were once thought to be wide‐ranging being delimited into multiple independent species. On the Southeast Asian island of Borneo, there has been a recent renewed focus on reptile taxonomy, as genetic data have demonstrated a high amount of unrecognised biodiversity. We herein advance this taxonomic trend by delimiting three distinct species within the Cyrtodactylus consobrinus species complex: C. consobrinus, C. kapitensis sp. n., and C. hutan sp. n. To do so, we use a combination of ddRADseq and single‐locus data, and morphological data. Using genomic data, we test species and population boundaries within the consobrinus species complex and show minimal population structure but high species‐level diversity. Despite not finding uniquely diagnostic morphological characters to delimit the new species, we suggest a combination of characters that can be used to identify each lineage. Lastly, we use our data to comment on the status of C. malayanus , with indications that this lineage is also better considered a species complex. These data highlight the prevalence of unrecognised lineages on Borneo, many of which face threats due to increasing deforestation and other anthropogenic pressures.

A Systematic Review of Culture-Based Methods for Monitoring Antibiotic-Resistant Acinetobacter, Aeromonas, and Pseudomonas as Environmentally Relevant Pathogens in Wastewater and Surface Water - Erin G. Milligan; Jeanette Calarco; Benjamin C. Davis; Ishi M. Keenum; Krista Liguori; Amy Pruden; Valerie J. Harwood (Current Environmental Health Reports, 2023)
Purpose of Review Mounting evidence indicates that habitats such as wastewater and environmental waters are pathways for the spread of antibiotic-resistant bacteria (ARB) and mobile antibiotic resistance genes (ARGs). We identified antibiotic-resistant members of the genera Acinetobacter , Aeromonas , and Pseudomonas as key opportunistic pathogens that grow or persist in built (e.g., wastewater) or natural aquatic environments. Effective methods for monitoring these ARB in the environment are needed to understand their influence on dissemination of ARB and ARGs, but standard methods have not been developed. This systematic review considers peer-reviewed papers where the ARB above were cultured from wastewater or surface water, focusing on the accuracy of current methodologies. Recent Findings Recent studies suggest that many clinically important ARGs were originally acquired from environmental microorganisms. Acinetobacter , Aeromonas, and Pseudomonas species are of interest because their ability to persist and grow in the environment provides opportunities to engage in horizontal gene transfer with other environmental bacteria. Pathogenic strains of these organisms resistant to multiple, clinically relevant drug classes have been identified as an urgent threat. However, culture methods for these bacteria were generally developed for clinical samples and are not well-vetted for environmental samples. Summary The search criteria yielded 60 peer-reviewed articles over the past 20 years, which reported a wide variety of methods for isolation, confirmation, and antibiotic resistance assays. Based on a systematic comparison of the reported methods, we suggest a path forward for standardizing methodologies for monitoring antibiotic resistant strains of these bacteria in water environments.

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

Improvement of mineral nutrition and rooting efficiency of Cannabis sativa L. for in vitro large-scale propagation - Adel Zarei; Benjamin Davis; Biruk A. Feyissa; Elham Tavakouli Dinani; Brigitte Simons (In Vitro Cellular & Developmental Biology - Plant, 2023)

The ASLO Multicultural Program Pioneers Diversity Efforts in the Aquatic Sciences - Benjamin Cuker; Jeanette Davis (Oceanography, 2023)
The Association for the Sciences of Limnology and Oceanography Multicultural Program (ASLOMP) began in 1990 as an effort to diversify participation in the aquatic sciences, with particular emphasis on increasing the number of BIPOC (Black, Indigenous, and people of color) in the field (Cuker, 2001, 2005, 2007). It was evident to anyone attending an ASLO meeting, or that of any other aquatic scientific society in the 1980s that BIPOC were essentially absent. The ranks of related academicians, agency workers, and students mirrored that absence of diversity. This was consistent with data gathered by the National Science Foundation (NSF) indicating that only 3% of doctorates earned in 1990 in the Earth, atmospheric, and ocean sciences were earned by underrepresented minorities (NSF, 1994). Acting on this information, the ASLO leadership constructed a program that would bring diverse students interested in the aquatic sciences to its annual meetings for special programming aimed at recruiting and retaining BIPOC in the aquatic and allied sciences and applied to NSF for funding.

Advancing Diversity and Inclusivity in Ocean Sciences by Re-Envisioning Overlooked Barriers in Scientific Diving Training - Paul Barber; Jeannie Barber-Choi; Austin Betancourt; Benjamin Cuker; Alexandra Davis; Caitlin Fong; Peggy Fong; Deidre Gibson; Tyler Smith (Oceanography, 2023)
Self-contained underwater breathing apparatus (scuba) is an essential tool in some marine science fields. However, financial costs and racial disparities in swimming participation can be a barrier to entry for many aspiring marine scientists of color. Scientific diving programs could improve access to scientific diving training by offering training as part of their standard undergraduate curriculum and by maintaining a stock of scuba gear for use during courses. Similarly, the American Academy of Underwater Scientists (AAUS) could make training more accessible by re-envisioning components of the swim test and by building water safety skills into AAUS training—​all without compromising safety. Combined, these two actions would expand pathways for students of color to careers in marine science, adding much needed diversity to the field.

A Low-Cost, DIY Ultrasonic Water Level Sensor for Education, Citizen Science, and Research - Philip Bresnahan; Ellen Briggs; Benjamin Davis; Angelica Rodriguez; Luke Edwards; Cheryl Peach; Nan Renner; Harry Helling; Mark Merrifield (Oceanography, 2023)
A low-cost (~$100), do-it-yourself (DIY) ultrasonic water level sensor/datalogger has been designed, constructed, and tested for use in education, citizen/community science, and research settings. The sensor package comprises an ultrasonic distance sensor, a microcontroller running Arduino firmware, a micro-SD card for datalogging, a real-time clock for timekeeping and sleep functions, and an OLED screen for real-time display. Electronics are housed in low-cost custom containers using either upcycled plastic containers or laser-cut acrylic. Reported ultrasonic sensor accuracy is 5 cm across a range of 15–645 cm, with an estimated power budget of 76 days of operation on a rechargeable 10 amp-hr battery. The DIY sensor has been field tested alongside two commercial sensors for 18 days in Wilmington, North Carolina, including during Tropical Storm Colin, with all sensor measurements in close agreement (e.g., root mean squared error of 1.5 cm between the DIY sensor and a proven commercial unit). Potential applications, design and construction, and deployment recommendations for the sensors are described, as well as simple and inexpensive modifications to the sensor and its packaging that could further improve performance. Preliminary lesson plans written to accompany the device for high school- and undergraduate-level educational projects are available.

A framework for standardized qPCR-targets and protocols for quantifying antibiotic resistance in surface water, recycled water and wastewater - Ishi Keenum; Krista Liguori; Jeanette Calarco; Benjamin C. Davis; Erin Milligan; Valerie J. Harwood; Amy Pruden (Critical Reviews in Environmental Science and Technology, 2022)

Duration- and sex-dependent neural circuit control of voluntary physical activity - Margaret K. Tanner; Jazmyne K. P. Davis; Jennifer Jaime; Nicolette A. Moya; Alyssa A. Hohorst; Kelsey Bonar; Kelsey A. Abrams; Nashra Jamil; Rebecca Han; Troy J. Hubert; Nadja Brown; Esteban C. Loetz; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Do not transform food systems on the backs of the rural poor - Benjamin Davis; Leslie Lipper; Paul Winters (Food Security, 2022)

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Mutational analyses of novel rat models with targeted modifications in inflammatory bowel disease susceptibility genes - Hongsheng Men; Miriam A. Hankins; Anagha S. Bock; Benjamin P. Beaton; Daniel J. Davis; Kari L. Chesney; Elizabeth C. Bryda (Mammalian Genome, 2021)
Mutations and single base pair polymorphisms in various genes have been associated with increased susceptibility to inflammatory bowel disease (IBD). We have created a series of rat strains carrying targeted genetic alterations within three IBD susceptibility genes: Nod2 , Atg16l1 , and Il23r, using CRISPR/Cas9 genome editing technology. Knock-out alleles and alleles with known human susceptibility polymorphisms were generated on three different genetic backgrounds: Fischer, Lewis and Sprague Dawley. The availability of these rat models will contribute to our understanding of the basic biological roles of these three genes as well as provide new potential IBD animal models.

Effects of Saltwater Pulses on Soil Microbial Enzymes and Organic Matter Breakdown in Freshwater and Brackish Coastal Wetlands - Shelby Servais; John S. Kominoski; Carlos Coronado-Molina; Laura Bauman; Stephen E. Davis; Evelyn E. Gaiser; Stephen Kelly; Christopher Madden; Viviana Mazzei; David Rudnik; Fabiola Santamaria; Fred H. Sklar; et al. (Estuaries and Coasts, 2020)

WormBot, an open-source robotics platform for survival and behavior analysis in C. elegans - Jason N. Pitt; Nolan L. Strait; Elena M. Vayndorf; Benjamin W. Blue; Christina H. Tran; Brendon E. M. Davis; Karen Huang; Brock J. Johnson; Keong Mu Lim; Sophie Liu; Arash Nikjoo; Anuj Vaid; et al. (GeroScience, 2019)

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Correction to: Development and Evaluation of Geostatistical Methods for Non-Euclidean-Based Spatial Covariance Matrices - Benjamin J. K. Davis; Frank C. Curriero (Mathematical Geosciences, 2019)

Development and Evaluation of Geostatistical Methods for Non-Euclidean-Based Spatial Covariance Matrices - Benjamin J. K. Davis; Frank C. Curriero (Mathematical Geosciences, 2019)

Declines in Plant Productivity Drive Carbon Loss from Brackish Coastal Wetland Mesocosms Exposed to Saltwater Intrusion - Benjamin J. Wilson; Shelby Servais; Sean P. Charles; Stephen E. Davis; Evelyn E. Gaiser; John S. Kominoski; Jennifer H. Richards; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Functional and Compositional Responses of Periphyton Mats to Simulated Saltwater Intrusion in the Southern Everglades - Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Benjamin J. Wilson; Shelby Servais; Laura Bauman; Stephen E. Davis; Steve Kelly; Fred H. Sklar; David T. Rudnick; Jemma Stachelek; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Limited genetic structure in a wood frog (Lithobates sylvaticus) population in an urban landscape inhabiting natural and constructed wetlands - Benjamin L. S. Furman; Brett R. Scheffers; Murdoch Taylor; Corey Davis; Cynthia A. Paszkowski (Conservation Genetics, 2016)

NMR-Based Metabolomics Separates the Distinct Stages of Disease in a Chronic Relapsing Model of Multiple Sclerosis - Alex M. Dickens; James R. Larkin; Benjamin G. Davis; Julian L. Griffin; Timothy D. W. Claridge; Nicola R. Sibson; Daniel C. Anthony (Journal of Neuroimmune Pharmacology, 2015)

Potential future land use threats to California’s protected areas - Tamara Sue Wilson; Benjamin Michael Sleeter; Adam Wilkinson Davis (Regional Environmental Change, 2015)

The role of photo-osmotic adaptation in semi-continuous culture and lipid particle release from Dunaliella viridis - Ryan W. Davis; Benjamin J. Carvalho; Howland D. T. Jones; Seema Singh (Journal of Applied Phycology, 2015)

Commitment to the environment and student support for “green” campus initiatives - Anthony E. Coy; Allison K. Farrell; Katharine P. Gilson; Jody L. Davis; Benjamin Le (Journal of Environmental Studies and Sciences, 2013)

Apodemia mormo in Canada: population genetic data support prior conservation ranking - Benjamin Proshek; Lindsay A. Crawford; Corey S. Davis; Sylvie Desjardins; Allison E. Henderson; Felix A. H. Sperling (Journal of Insect Conservation, 2013)

Recommendations for ethical approaches to genotype-driven research recruitment - Laura M. Beskow; Stephanie M. Fullerton; Emily E. Namey; Daniel K. Nelson; Arlene M. Davis; Benjamin S. Wilfond (Human Genetics, 2012)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Photoluminescence Properties of Conjugated Phenylacetylene Monodendrons in Thin Films - Joseph S. Melinger; Benjamin L. Davis; Dale McMorrow; Yongchun Pan; Zhonghua Peng (Journal of Fluorescence, 2004)

Book reviews - Gerard L. Coté; Nasreen Haideri; Yadin David; William A. Hyman; Roy B. Davis; Benjamin S. Kelley; Timothy W. King (Annals of Biomedical Engineering, 1992)